PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL DAN TRANSAKSIONAL SERTA KEPUASAN KERJA TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) PADA PT.INDOFOOD SUKSES MAKMUR BEJI PASURUAN - LEMBONO, ARDI YULIANTO (Universitas Katolik Widya Mandala Surabaya, 2013)
A leader must be able to influence subordinates to carry out the task without force commanded so voluntarily subordinates will behave and perform as demanded by the organization through leadership directives. Transactional and transformational leadership was developed based on the opinion of the level of Maslow's human needs. Job satisfaction (job satisfaction) is the emotional state of employees who happen or not happen the meeting point between the value of employee remuneration and company or organization with a level of remuneration values that are desired by the employee concerned. Organizational citizenship behavior (OCB). Organizational citizenship behavior (OCB) is a behavior that is not part of the task that has been formally required for an employee but as a whole encourage the effective functioning of the organization. In any study of transactional and transformational leadership and job satisfaction was found to have a close relationship with organizational citizenship behavior. Therefore, this study will provide more in-depth study on the effect of transformational and transactional leadership styles and job satisfaction on organizational citizenship behavior. Used in this study are conclusive research on experimental studies or causal research. Sampling technique used was non-probability sampling. Type of method used was purposive sampling. The samples used were 100 employees of PT. Indofood Sukses Makmur Beji Pasuruan. Data was collected using questionnaires. The analysis technique used is multiple linear regression analysis with SPSS. Results of this analysis showed that transformational and transactional leadership style and satisfaction kerjaberpengaruh the organizational citizenship behavior of employees of PT. Indofood Sukses Makmur Beji Pasuruan.